Improving a tempering machine for confectionery masses - Zahorulko, Andrii; Zagorulko, Aleksey; Kasabova, Kateryna; Liashenko, Bogdan; Postadzhiev, Alexander; Sashnova, Mariana (Eastern-European Journal of Enterprise Technologies, 2022)
This paper reports the improved model of a tempering machine for heating the formulation mixture of marshmallow, characterized by heat supply to the working tank through the replacement of a steam jacket with heating by a film resistive electric heater of radiative type (FREhRT). The surface of the heat exchange of the device was increased by heating the stirrer with FREhRT; secondary energy (30....85 °C) was used by converting it by Peltier elements for the autonomous operation of superchargers for cooling the engine compartment. The proposed solution will lead to an increase in the efficiency of the device, which is explained by a decrease in its specific metal consumption through the use of FREhRT. A reduction in the duration of heating (75 °C) a marshmallow formulation mixture was experimentally established: in the examined model, 530 s, compared with the analog, 645 s. That confirmed the reduction in heating time to the set temperature by 21.7 % compared to the MT-250 basic design. The calculations have established a decrease, by 13 %, in the specific energy consumption for heating the volume of a unit of product when using the improved structure, 205.7 kJ/kg, when using the basic one ‒ 232.1 kJ/kg. The increase in the efficiency of the proposed structure is explained by a decrease in the specific metal consumption of the device from 474 kg/m2 in the base apparatus to 273 kg/m2 in the improved one. The study results confirm the increase in the resource efficiency of the improved tempering machine, which is achieved by eliminating the steam jacket; increasing the heat exchange surface by heating the stirrer. The heat transfer by FREhRT simplifies the operational performance of the temperature stabilization system in a working tank. The reported results could prove useful when designing thermal devices with electric heat supply under the conditions of using secondary energy, which is relevant for ensuring resource efficiency